Effect of Financial Literacy And Financial Behavior On Customers' Gold Investment Interest at PT. Pegadaian Unit Palopo - Naifa Saputri; Samsul Bachri; Rahmawati Rahmawati (Perkumpulan Dosen Muda (PDM) Bengkulu, 2026)
Purpose: The low level of financial literacy and public financial behavior is a challenge in increasing investment interest, especially relatively safe investments such as gold. The purpose of this study is to analyze how financial literacy and financial behavior influence the interest in gold investment of customers at PT. Pegadaian Unit Palopo. Methodology: The method used is a quantitative approach with a population of 671 customers and a sample of 87 respondents determined by the Slovin formula. Data collection was carried out by distributing questionnaires, then analyzed using multiple linear regression in SPSS version 16.0. Results: The findings of the study indicate that Financial Literacy and Financial Behavior, both partially and simultaneously, have a positive and significant impact on Customer Gold Investment Interest at PT. Pegadaian Unit Palopo. Findings: The findings confirm that better financial understanding and regular financial behavior patterns enhance investment interest. Novelty & Originality: This study offers novelty by examining gold investment interest in a regional pawnshop context in Palopo, a setting rarely explored in prior research. Conclusions: The implications of this study indicate that increasing financial literacy and good financial behavior can encourage public interest in investing in gold. Type of Paper: This paper is an empirical research paper.